Defilement of virgins in biblical law and the case of Dinah (Genesis 34) - Rofe, Aleksander (Biblica, 2005)
Seduction or rape of a virgin in the Biblical milieu did not signify her being defiled. The Hebrew verb ṭimme' (to defile) applied to married or betrothed women only. The case of Dinah is an exception. In Genesis 34, it is stated three times that Jacob's daughter was defiled by Shechem (vv. 5.13.27). A plausible explanation of this state of affairs is that Genesis 34 reflects the late, postexilic notion that the idolatrous gentiles are impure which implies the prohibition of intermarriage and intercourse with them (Ezra 9,11-12). The concept of the impurity of idolaters persisted in post-biblical literature. Thus, the assertion that Dinah was defiled by Shechem betrays a late date of composition in respect of this story. This confirms Kuenen's hypothesis that Genesis 34 in its present form is a late chapter, containing an anti-Samaritan polemic which originated in the Restoration Community of the Fifth-Fourth centuries BCE.